Effect of different levels of sugar on qualitative characteristics of lassi prepared from sour dahi - Moazzem, Muhammad Shah; Islam, Md Nurul; Masum, A K M; Habib, Md Rezwanul (Fundamental and Applied Agriculture, 2018)
An investigation was carried out to develop lassi from sour dahi using dif- ferent levels of sugar (10, 15, 20 and 25%) and 15% water. Lassi quality was assayed through the study of physical, chemical and microbiological parameters. Results revealed that significant difference existed in overall physical score of lassi samples and the highest score was found in 15% sugar lassi whereas, the lowest score was found in 25% sugar lassi. Total solids, carbohydrate, fat, protein and ash contents differed significantly among var- ious levels of sugar added lassi. From chemical test, it appears that, 15% sugar added lassi possess the highest fat and protein values whereas, the highest total solids and carbohydrate values posses in 25% sugar added lassi. No significant difference (p>0.05) revealed in terms of pH value and acidity percentage among lassi types. Lassi made from 10% sugar was most inferior than other levels of sugar added lassi in respect of microbiological quality- total viable count (×104 cfu/mL) content was 95.67±2.08 and coliform (×10 cfu/mL) content was 1.00±0.00. Considering above mentioned quality as- pects, it might be resolved that lassi could be prepared successfully from sour dahi with 15% sugar keeping water level constant at 15%.